2008
DOI: 10.2527/jas.2008-0916
|View full text |Cite
|
Sign up to set email alerts
|

Central role of the melanocortin-4 receptors in appetite regulation after endotoxin1

Abstract: Melanocortin-4 receptors (MC4R) are key factors in the depression of appetite during disease. This study was designed to determine the role of agouti-related protein (AgRP) in the effect of endotoxin (lipopolysaccharide, LPS) on appetite. Sheep received an intracerebroventricular injection of either saline or AgRP (0.5 nmol/kg of BW) 1 h before intravenous injection of either saline or LPS (0.6 microg/kg of BW) at time 0 and again at 4 h. Agouti-related protein prevented the reduction in feed intake due to LPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
32
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 33 publications
4
32
0
Order By: Relevance
“…The effect was present between 4 and 12 h, but unlike other animal models, the effect on feed intake did not persist to 24 h (Wagner et al, 2004). Examination of whether altered AgRP expression contributed to reduced feed intake after endotoxin injection determined that there were no changes in AgRP expression during the early phase of appetite suppression (Sartin et al, 2008). In another experiment, AgRP injected before endotoxin prevented the inhibition of appetite (Sartin et al, 2008) characteristic of endotoxin treatment.…”
mentioning
confidence: 88%
See 3 more Smart Citations
“…The effect was present between 4 and 12 h, but unlike other animal models, the effect on feed intake did not persist to 24 h (Wagner et al, 2004). Examination of whether altered AgRP expression contributed to reduced feed intake after endotoxin injection determined that there were no changes in AgRP expression during the early phase of appetite suppression (Sartin et al, 2008). In another experiment, AgRP injected before endotoxin prevented the inhibition of appetite (Sartin et al, 2008) characteristic of endotoxin treatment.…”
mentioning
confidence: 88%
“…In sheep, in situ hybridization studies clearly localize POMC to the ARC (Henry et al, 2000;Clarke et al, 2000;Lincoln et al, 2001;Adam et al, 2002). In addition, immunohistochemical evidence for a-MSH (product of the POMC gene) was likewise found in the ARC (Sartin et al, 2008). In one study, POMC gene expression in the ARC was found to be unaffected by a short-term (4-day) fast .…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…The melanocortin-4 receptor (MC4R) 12 gene, which is primarily expressed in the brain (1), participates in complex neurohormonal pathways with reciprocal effects on energy intake and expenditure (2)(3)(4)(5), primarily through its regulatory effect on appetite and satiety (6). MC4R is also a key factor in regulating body adiposity (7).…”
Section: Introductionmentioning
confidence: 99%